ChemInform Abstract: Series of Lead Oxide Hydroxide Nitrates Obtained by Adjusting the pH Values of the Reaction Systems. Issue 29 (22nd July 2014) - Wang, Genxiang; Luo, Min; Ye, Ning; Lin, Chensheng; Cheng, Wendan
Abstract Pb(II) oxide hydroxide nitrates are prepared under subcritical hydrothermal conditions by adjusting the pH values of the Pb(NO3)2—NaOH reaction system.